(untitled) (Research, Society and Development, 2022)
The research aimed to analyze the prevalence, laboratory diagnosis and treatment of syphilis during pregnancy. It was an integrative literature review, in which the SciELO, LILACS and VHL databases were used, by crossing the descriptors: Laboratory diagnosis, Pregnancy, Prevalence, Syphilis and Treatment. The research was guided by the following questions: How is the treatment, laboratory diagnosis and the prevalence of syphilis in pregnancy currently? What are the public health policies of the Unified Health System (SUS) aimed at gestational syphilis. A total of 5,364 publications were found, which, after meeting the inclusion and exclusion criteria, were filtered and 10 publications were selected, which made up the final sample of the study. The articles chosen were between the years 2016 to 2022. The main findings of the study showed that Gestational Syphilis and Congenital Syphilis have victimized mothers and babies and challenged the health system with regard to tracking, treatment and eradication of the disease . It is evident the need for actions aimed at reducing vertical transmission of syphilis, expanding access to diagnostic methodologies, in addition to serological screening, these attributions reinforce the prevention of the disease and the reduction of possible sequelae. It is concluded, therefore, that poor quality and inadequate prenatal care contributes to the emergence of failures in the treatment of pregnant women, which may possibly result in congenital cases of syphilis. Therefore, it is of fundamental importance to promote health actions that aim to eliminate the vertical transmission of syphilis.